The investigation of the impact of education on sexual health/reproductive health knowledge levels of nurses and midwives in extraordinary situations – evidence from Turkey - Cirban Ekrem, Ebru; Kuş, Tuğçe; Erkmen, Emir; Dursun, Nisanur (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. In extraordinary situations, sexual/reproductive health services are very important for the health of the whole society, especially women and children. The aim of this study is to assess the impact of training provided on sexual health/reproductive health during extraordinary situations on the knowledge levels of nurses and midwives. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The research was conducted using a single-group pre-test-post-test follow-up test measurement quasi-experimental design. It was completed between November 2021–June 2022 with 140 participants working in a province in Turkey. The data were collected with the “Descriptive Information Form” and the “Sexual Health and Reproductive Health Knowledge Assessment Form for Extraordinary Situations”. Training was given with the Sexual Health/Reproductive Health Training Booklet for Extraordinary Situations. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. It was found that the participants scored 20.82±4.47 on the Sexual Health and Reproductive Health Knowledge Assessment Form for Extraordinary Situations in the pre-test, 27.63±2.67 in the post-test, and 27.07±3.46 in the follow-up test. As a result of the training, it was determined that the difference between the scores they got from the Sexual Health and Reproductive Health Knowledge Assessment Form for Extraordinary Situations was due to the pre-test (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In the study, the participants scored above the average in the pre-test, while they achieved significantly higher scores in the post-test and follow-up test. This shows that the training given to nurses and midwives is effective.